Photochromic Naphthopyran Dyes Incorporating a Benzene, Thiophene, or Furan Spacer: Effect on Photochromic, Optoelectronic, and Photovoltaic Properties in Dye‐Sensitized Solar Cells. Issue 8 (15th December 2021) - Liotier, Johan; Mwalukuku, Valid Mwatati; Fauvel, Samuel; Riquelme, Antonio J.; Anta, Juan A.; Maldivi, Pascale; Demadrille, Renaud
Abstract : It is recently demonstrated that diaryl‐naphthopyran photochromic dyes are efficient for sensitization of TiO2 mesoporous electrodes, thus allowing the fabrication of photochromo‐voltaic cells that can self‐adapt their absorption of light and their generation of electricity with the light intensity. Herein, the synthesis and characterization of two photochromic dyes based on a diaryl‐naphthopyran core, NPI‐ThPh and NPIFuPh, for use in dye sensitized solar cells is reported. Compared to the reference dye NPI, the molecules vary by the nature of the spacer, a thiophene or a furan, connecting the photochromic unit and the anchoring function. It was found that swapping a phenyl for a thiophene or a furan leads to an improvement of the absorption properties of the molecules, both in solution and after grafting on TiO2 electrodes, however their photochromic process becomes not fully reversible. Despite better absorption in the visible range, the new dyes show poorer photochromic and photovoltaic properties in devices compared to NPI. Thanks to UV–Vis spectroscopy, theoretical modelling, electrical characterization of the cells, and impedance spectroscopy, the factors limiting their performances have been unraveled. This study contributes to better understand the connection between photochromic and photovoltaic properties, which is key to develop better performing molecules of this class. Abstract : Two new photochromic photosensitizers for use in dye‐sensitized solar cells are reported. Thanks to UV–vis spectroscopy, density‐functional theory calculations, electrical and impedance spectroscopy characterizations of the solar cells, important relationships between structure, photochromic and photovoltaic properties within this novel class of multifunctional dyes have been unraveled.